Effect of sowing date and Treflan herbicide on the growth and yield of local barley, Hordeum vulgare - Jasim Hayawi (مجلة جامعة كركوك للعلوم الزراعية)
In order to reach the best date for planting the barley crop after spraying the herbicideTrflan with different concentrations, this study was conducted during the agriculturalseason 2020-2021 at the Agricultural Technical College / Mosul. The experiment wasapplied on the factorial system of experiments, in RCBD, with three replications. Thefirst factor: the planting date after spraying the herbicide and at three levels (cultivationimmediately after spraying, cultivation one week after spraying the herbicide,cultivation two weeks after spraying the herbicide) . The second factor: theconcentration of the herbicide at four levels (0, 2200, 2600, 3000) cm3 . ha-1. , (whichis the control treatment, less than the recommended concentration, the recommendedconcentration and higher than the recommended concentration) .The results obtainedare summarized as follows:- The cultivation after a week of spraying the herbicide Treflan achieved the best resultsin all the studied traits.- The use of a low concentration of Treflan (2200 cm3.ha-1) achieved the best resultscompared to high concentrations.- The interaction between the sowing date was achieved after a week of spraying theherbicide, Treflan, with a concentration of 2200 cm3. ha-1 has the best results and forall studied traits.